2022
DOI: 10.1002/suco.202100670
|View full text |Cite
|
Sign up to set email alerts
|

Size effect and strain rate effect on seismic behavior of reinforced concrete beam‐column joints

Abstract: The mechanical behavior of reinforced concrete (RC) beam-column joints with different sizes under cyclic loads at varying rates was investigated, aiming at attaining a better understanding of the size effect and strain rate effect on RC beam-column joints. First, a 2D mesoscale numerical model was established and verified by existing experimental results. Second, numerical tests regarding seismic performances of RC beam-column joints were carried out. A total of four structural sizes and five strain rates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…Numerous studies and research have been devoted to exploring and knowing the strain rate on structural member responses. 48 Still, this research hotspot remains open to discussion for all research studies, particularly concerning the high-velocity impact. Detailed examinations on strength increment can be determined by dynamic increase factor (DIF) for compressive and tensile strength with a given strain rate as typically.…”
Section: Strain-rate Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies and research have been devoted to exploring and knowing the strain rate on structural member responses. 48 Still, this research hotspot remains open to discussion for all research studies, particularly concerning the high-velocity impact. Detailed examinations on strength increment can be determined by dynamic increase factor (DIF) for compressive and tensile strength with a given strain rate as typically.…”
Section: Strain-rate Effectsmentioning
confidence: 99%
“…By examining the effect of strain rates under the influence of impact loads, concrete and steel have high sensitivity; therefore, it is critical to include the effect of concrete and steel strain in numerical simulation. Numerous studies and research have been devoted to exploring and knowing the strain rate on structural member responses 48 . Still, this research hotspot remains open to discussion for all research studies, particularly concerning the high‐velocity impact.…”
Section: Strain‐rate Effectsmentioning
confidence: 99%
“…Moreover, available scientific data outline that the size effect is more significant for concrete specimens with obvious brittleness. [26][27][28][29][30] Jin et al 31 conducted an experiment on RC beam-column joints with different structural sizes, particularly large specimens (the maximum section size of largest joint is 900 Â 900 mm), and found that size effect on shear strength of joints with shear failure was significant.…”
Section: Size Effect On Rc Beam-column Jointmentioning
confidence: 99%
“…These experiment results showed that when the structural size increased, the shear strength of joints decreased, namely the size of joint had a significant effect on the nominal shear strength. Moreover, available scientific data outline that the size effect is more significant for concrete specimens with obvious brittleness 26–30 . Jin et al 31 conducted an experiment on RC beam‐column joints with different structural sizes, particularly large specimens (the maximum section size of largest joint is 900 × 900 mm), and found that size effect on shear strength of joints with shear failure was significant.…”
Section: Introductionmentioning
confidence: 99%
“…The consistent research findings are concluded that as the loading rate increases, both the tensile strength and compressive strength of concrete, the yield strength and ultimate strength of reinforcement are magnified, and the elastic modulus and the strain corresponding to the compressive strength of concrete are also affected by the loading rate [2]. As for structural members consisting of RC materials, such as columns [3][4][5][6], beams [7][8][9][10][11][12][13][14], shear walls [15][16][17][18][19] and joints [20][21][22][23][24][25], changes in mechanical behaviors to different degrees are observed for specimens under various loading rates, namely the dynamic effect at the member level. Different failure patterns of RC structural members could be observed in seismic hazards, as shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%